Natural killer cells trigger differentiation of monocytes into dendritic cells. - Zhang, A; Colmenero, P; Purath, U; Teixeira de Matos, C; Hueber, W; Klareskog, L; Tarner, I; Engleman, E; Söderström, K (2007)
Circulating monocytes can differentiate into dendritic cells (moDCs), which are potent inducers of adaptive immune responses. Previous reports show that granulocyte macrophage-colony-stimulating factor (GM-CSF) and interleukin-4 induce monocyte differentiation into moDCs in vitro, but little is known about the physiological requirements that initiate moDC differentiation in vivo. Here we show that a unique natural killer (NK) cell subset (CD3(-)CD56(bright)) that accumulates in lymph nodes and chronically inflamed tissues triggers CD14(+) monocytes to differentiate into potent T-helper-1 (T(H)1) promoting DC. This process requires direct contact of monocytes with NK cells and is mediated by GM-CSF and CD154 derived from NK cells. It is noteworthy that synovial fluid (SF) from patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA), but not osteoarthritis (OA), induces monocytes to differentiate into DC. However, this process occurs only in the presence of NK cells. We propose that NK cells play a role in the maintenance of T(H)1-mediated inflammatory diseases such as RA by providing a local milieu for monocytes to differentiate into DC.